1990
DOI: 10.1016/s0022-5347(17)39571-x
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Ileal Neobladder due to Urethral Obstruction by Mucous Plug

Abstract: We report a case of ileal neobladder rupture after radical cystectomy due to mucus obstruction of the bladder neck. Since mucus production in bowel neobladders cannot be sufficiently influenced pharmacologically, patients with a continent urinary diversion connected to the urethra should learn self-catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…On average, the patients were followed for 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months, when both objective and subjective parameters had been prospectively studied. Objective parameters were evaluated by urodynamic examination, imaging methods and laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, the patients were followed for 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months, when both objective and subjective parameters had been prospectively studied. Objective parameters were evaluated by urodynamic examination, imaging methods and laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal segments produce mucus in the amount of 37 g/day [27]. The mucus can mechanically obstruct the urethra in 3% of patients [10], which results in postmicturition residual urine and rarely in perforation of the bladder [7,28]. Another negative property of the mucus is its lithogenic potential and the increased risk of infection [28,29].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of life of these patients is affected by recurrent urinary tract infections, stone formation, excessive mucus production and an increased risk of colonic neoplasia leading to malignancy [27][28][29]. Indeed, many studies have demonstrated that in artificial urinary bladder, secretomotor function is maintained in the long term with mucus production and problems related to its excessive production are not decreasing with time [30][31][32][33][34]. Over the past 15 years, the proportion of patients receiving a neobladder has increased significantly and it becomes necessary to characterize the changes in mucin expression and glycosylation in transposed segments to better understand the relation structure/function of these proteins under abnormal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…tive early and late complications as well as the metabolic consequences of this technique have been examined extensively [2,[6][7][8][9][10][11][12][13][14] . In contrast to orthotopic neobladders, where ruptures obviously occur more often and have therefore been described in detail [14][15][16][17][18][19][20][21][22][23] , ruptures of heterotopic continent ileocecal reservoirs have only been mentioned in individual case reports or as part of nationwide surveys [24][25][26] , mostly due to their sporadic occurrence.…”
mentioning
confidence: 99%